Nitrogen physiology of contrasting genotypes of Chenopodium quinoa Willd. (Amaranthaceae). Issue 1 (December 2018) - Bascuñán-Godoy, Luisa; Sanhueza, Carolina; Pinto, Katherine; Cifuentes, Leonardo; Reguera, María; Briones, Vilbett; Zurita-Silva, Andrés; Álvarez, Rodrigo; Morales, Andrea; Silva, Herman
Abstract Quinoa has been highlighted as a promising crop to sustain food security. The selection of physiological traits that allow identification genotypes with high Nitrogen use efficiency (NUE) is a key factor to increase Quinoa cultivation. In order to unveil the underpinning mechanisms for N-stress tolerance in Quinoa, three genotypes with similar phenology, but different NUE were developed under high (HN) or low (LN) nitrogen conditions. N metabolism processes and photosynthetic performance were studied after anthesis and in correlation with productivity to identify principal traits related to NUE. We found that protein content, net photosynthesis and leaf dry-mass were determinant attributes for yield at both HN and LN conditions. Contrastingly, the enhancement of N related metabolites ( $${{\rm{NH}}}_{4}^{+}$$ NH 4 +, proline, betacyanins) and processes related with re-assimilation of $${{\rm{NH}}}_{4}^{+}$$ NH 4 +, including an increment of glutamine synthetase activity and up-regulation ofCqAMT1, 1 transporter expression in leaves, were negatively correlated with grain yield at both N conditions. Biochemical aspects of photosynthesis and root biomass were traits exclusively associated with grain yield at LN. The impact of N supply on seed quality is discussed. These results provide new insights towards the understanding the N metabolism of Quinoa.